The effect of layer diets supplemented with zeolit on production performance - Tahir Balevi; Behiç Coşkun; Erdoğan Şeker; Varol Kurtoğlu (Eurasian Journal of Veterinary Sciences)
At present study 320 Babcock-B-380 brown hens aged 32 week were used. This experiment was carried out to determine effects of feeding laying diets suppfemented with different levels of Clinut-1000 (0, 1.5, 2.5 and 3.5%) on their feed intake, feed efficiency, egg production, egg weight, damaged egg ratio and specific gravity. The experiment was lasted in 90 days. At the end of the experiment egg production was found to be 90.76, 92.10, 91.62 and 90.61 %, respectively (P>0.005). Feed intake was observed to be 135.44, 135.12, 129.09 and 129.25 g, respectively (P>0.05). While the lowest feed efficiency (2.29) was obtained in the group fed 3.S % zeolit, the highest feed efficiency (2.40) was obtained in the group feed 0 % Zeolit (P>O.OS). There were no differences between the groups in terms of egg weight and specific gravity (P>0.05). Middle of the experiment. while the lowest ratio for damaged egg(1%) was obtained in the group fed 1.5 % Zeolit-1000, the highest ratio for damaged egg (1.31 %) was obtained in the group fed 0 % Zeolit At the end of the experiment, ratio of damaged egg was determined to be 0.94, 0.78, 1.19 and 1.05 %, respectively. Consequently, use of levels of 2.5 and 3.5 % Zeolit in poultry diets was concluded to effect on feed conversion in a positive manner due to reduced feed intake without any reduction on egg production although differences showed no significance.